Mechanism Study of the Glycerol Oligomerization Reaction using Ab Initio Method - Muhammad Yusuf (Pascasarjana Universitas Negeri Medan, 2017)
Abstract: The mechanism study of the glycerol oligomerization reaction was performed to obtain the most possible diglycerol product based on its optimized energy. The mechanism study of the glycerol oligomerization reaction has been investigated regarding to SN2 type route with using HyperChem computer software, ab initio method, and 6-31G* basis set for all atom. Based on the computational calculation results, the energy level of the interaction between base catalyst (NaOH) with glycerol was similar in the α or β-anionic glycerol position (529.38kJ/mol). These results indicate the interaction of base catalyst (NaOH) with glycerol in the α or β-anionic glycerol position shows same possibility energetically favored. However, based on the computational calculation of diglycerol product, αα’-linear diglycerol more possible formed than αβ-branched diglycerol and ββ’-branched diglycerol due to its lowest energy (-0.19 kJ/mol). These results show that the fast attack of polarized glycerol to a carbon of a second glycerol will easier develop when the product is a αα'-linear diglycerol. The next step is formation of linear triglycerol from αα'-linear diglycerol which the difference of energy with glycerol is 6.83 kJ/mol. Keywords: ab initio, diglycerol, HyperChem, oligomerization